A comprehensive scoping review of ability and disability in ADHD using the International Classification of Functioning, Disability and Health-Children and Youth Version (ICF-CY) - de Schipper, E.; Lundequist, A.; Wilteus, A.; Coghill, D.; de Vries, P.; Granlund, M.; Holtmann, M.; Jonsson, U.; Karande, S.; Levy, F.; Al-Modayfer, O.; Rohde, L.; et al. (SPRINGER, 2015)
This is the first in a series of four empirical investigations to develop International Classification of Functioning, Disability and Health (ICF) Core Sets for Attention Deficit Hyperactivity Disorder (ADHD). The objective here was to use a comprehensive scoping review approach to identify the concepts of functional ability and disability used in the scientific ADHD literature and link these to the nomenclature of the ICF-CY. Systematic searches were conducted using Medline/PubMed, PsycINFO, ERIC and Cinahl, to extract the relevant concepts of functional ability and disability from the identified outcome studies of ADHD. These concepts were then linked to ICF-CY by two independent researchers using a standardized linking procedure. Data from identified studies were analysed until saturation of ICF-CY categories was reached. Eighty studies were included in the final analysis. Concepts contained in these studies were linked to 128 ICF-CY categories. Of these categories, 68 were considered to be particularly relevant to ADHD (i.e., identified in at least 5 % of the studies). Of these, 32 were related to Activities and participation, 31 were related to Body functions, and five were related to environmental factors. The five most frequently identified categories were school education (53 %), energy and drive functions (50 %), psychomotor functions (50 %), attention functions (49 %), and emotional functions (45 %). The broad variety of ICF-CY categories identified in this study underlines the necessity to consider ability and disability in ADHD across all dimensions of life, for which the ICF-CY provides a valuable and universally applicable framework. These results, in combination with three additional preparatory studies (expert survey, focus groups, clinical study), will provide a scientific basis to define the ICF Core Sets for ADHD for multi-purpose use in basic and applied research, and every day clinical practice.